PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 21 PEKANBARU - Prinawati '; Syahrifuddin '; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the low mathematics learning outcomes of students, with an average grade 62.28. While the value of a minimum completeness criteria (KKM) IPS is 70. Among the students numbering 35 people only 14 students who reach KKM with classical completeness 40%. This study is a Classroom Action Research (CAR) conducted aims to improve mathematics learning outcomes third grade students of SD State 21 Pekanbaru to implement cooperative learning model type Numbered Head Together. Formulation of the problem: Is the implementation of cooperative learning model Numbered Head Together mode can improve mathematics learning outcomes third grade students of SD Negeri 21 Pekanbaru. The research was conducted on 6 April 2015 through to 23 April 2015 with 3 cycles. The subjects were the third grade students of SD State 21 Pekanbaru totaling 35 which is used as a data source. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of learning derived from the value of daily tests before treatment with an average of 62.28, an increase in the first cycle with the average being 71.71. In the second cycle increased by an average of 76.71 and an increase in the third cycle with an average of 83.41. The activities of teachers in the learning process in cycle 1 the first meeting and the second meeting of the 71.87% increase to 75%. Second cycle of the first meeting and the second meeting of the 78.12% increase to 81.25%. In the third cycle of the first meeting and the second meeting of the 87.5% increase to 93.75%. Results of the data analysis activities of students in the first cycle of the first meeting with an average of 59.37% and the second meeting increased to 65.62%. Second cycle of the first meeting and the second meeting of the 75% increase to 78.12%. In the third cycle of the first meeting and the second meeting of the 84.37% increase to 90.62%. Results of the study in class III SD State 21 Pekanbaru prove that the implementation of cooperative learning model Numbered Head Together mode can improve mathematics learning outcomes third grade students of SD State 21 Pekanbaru.Key Words : Model Cooperative Learning, Results Learning mathematics